Development of in vitro Models for Delivery of the Anti-Viral Drug Acyclovir for Ocular HSV-I Infection Treatment - Bareiss, Bettina (University of Ottawa (Canada), 2010)
Herpes simplex virus 1 (HSV-1) infection is the main cause of vision loss in the developed world due to the fact that after initial infection, the virus establishes latency and can be reactivated; resulting in a very low success rate of treatment by transplantation (22%). We are developing corneal substitutes suitable for HSV-1 transplantation by incorporating anti-viral drugs such as acyclovir (ACV), into corneal substitutes that could potentially suppress the viral reactivation. Specifically, we examined the feasibility of preventing viral reactivation during surgery, by sustained delivery of ACV introduced during corneal transplantation surgery, through encapsulation of the drug within silica (SiO2) nanoparticles (NP) incorporated into biosynthetic alternatives to donor corneas. We show that incorporation of NPs did not affect optical clarity of the collagen-based corneal substitutes nor their biocompatibility. NP-encapsulation effectively sustained ACV release from the biosynthetic implants over 10 days, compared to free ACV incorporated directly into the hydrogel constructs. The NP-enabled sustained release resulted in effective prevention of virally-induced cell death, not observed with the free drug. This early model demonstrates the feasibility of using biomimetic corneal substitutes that incorporate a drug release system (e.g. silica nanoparticles encapsulating ACV) as future alternatives to human donor tissue grafts, for transplantation of HSV-infected corneas.
Keywords: Biology, Molecular.